2019
DOI: 10.1186/s41182-019-0163-8
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of frontline nurses with adverse medical events in a regional referral hospital in northern Ghana: a cross-sectional study

Abstract: Background Adverse medical events (AMEs) are threats to delivery of quality healthcare services, particularly in resource-poor settings such as Ghana. In sub-Saharan Africa, 30% of deaths are attributed to AMEs and a significant proportion of these events are not reported. This study explored personal experiences of nurses with AMEs and the constraints to reporting them. Methods This is a descriptive cross-sectional study among professional ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
3
11
1
Order By: Relevance
“…Indeed, increasing years of work experience had a negative association with adherence likelihood. This observation is contrary to similar studies where years of work associated with better professional practices by nurses and other clinical personnel [12,26,32]. Perhaps, the differences in methodology, cadre of respondents and clinical settings could explain these variances in findings.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Indeed, increasing years of work experience had a negative association with adherence likelihood. This observation is contrary to similar studies where years of work associated with better professional practices by nurses and other clinical personnel [12,26,32]. Perhaps, the differences in methodology, cadre of respondents and clinical settings could explain these variances in findings.…”
Section: Discussioncontrasting
confidence: 84%
“…In line with findings in some of the reviewed literature, it was found that even though over two thirds of the staff demonstrated knowledge of standard policy protocols, similar to findings by [7,12,26,27], there was an incommensurate application of the knowledge in real practice of their duties.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…protocols of nursing care. In line with findings in some of the reviewed literature, it was found that even though more than two thirds of the staff demonstrated knowledge of standard policy protocols, similar to previous studies [7,12,25,27], this knowledge did not translate into practice in terms of executing their duties. Alhassan et al [12] made similar observations when they discovered that even though nurses knew of the NMC policy guidelines for nasogastric tube feeding, majority of them, regrettably, did not apply this knowledge in the execution of their duties when independently observed.…”
Section: Plos Onesupporting
confidence: 80%
“…Sadly, adherence to these policy protocols to the latter remains a mirage in many healthcare facilities, especially those owned by government. Beyond the financial and infrastructural limitations confronting many of these health facilities, several empirical studies have pointed to wanton nonadherence to these professional guidelines on the part of clinicians, particularly nursing staff who turn to perform more of these clinical roles [12,25]. Obs.…”
Section: Discussionmentioning
confidence: 99%